2006
DOI: 10.1259/dmfr/44987850
|View full text |Cite
|
Sign up to set email alerts
|

Pyle's disease: an incidental finding in a routine dental patient

Abstract: Pyle's disease (PD) or metaphyseal dysplasia is an extremely rare genetic disorder, transmitted as an autosomal recessive trait. The peculiarity of the disease is that the striking radiographic manifestations contrast with the relatively normal clinical features. The oral findings and radiographic features of the disease are not well documented. The present paper describes the radiographic features of Pyle's disease in a 17-year-old girl and draws attention to the findings in the jaw bones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In mice, Sfrp4 expression is markedly increased in osteopenic accelerated-aging SAMP6 mice and manipulations of Sfrp4, globally or specifically in cells of the osteoblast lineage, lead to specific trabecular and cortical bone phenotypes (10)(11)(12). We have recently shown that SFRP4 loss-of function mutations cause Pyle's disease (OMIM 265900) (13), a rare autosomal recessive skeletal dysplasia characterized, in both genders, by wide metaphyses with increased trabecular bone, significant cortical thinning, fractures, and thin calvarium (13)(14)(15)(16)(17)(18)(19)(20)(21). In female and male mice, Sfrp4 genetic inactivation causes skeletal deformities closely mimicking those seen in humans: increased trabecular bone formation and decreased cortical thickness, due to impaired periosteal and endosteal bone formation and increased endosteal resorption (13).…”
mentioning
confidence: 99%
“…In mice, Sfrp4 expression is markedly increased in osteopenic accelerated-aging SAMP6 mice and manipulations of Sfrp4, globally or specifically in cells of the osteoblast lineage, lead to specific trabecular and cortical bone phenotypes (10)(11)(12). We have recently shown that SFRP4 loss-of function mutations cause Pyle's disease (OMIM 265900) (13), a rare autosomal recessive skeletal dysplasia characterized, in both genders, by wide metaphyses with increased trabecular bone, significant cortical thinning, fractures, and thin calvarium (13)(14)(15)(16)(17)(18)(19)(20)(21). In female and male mice, Sfrp4 genetic inactivation causes skeletal deformities closely mimicking those seen in humans: increased trabecular bone formation and decreased cortical thickness, due to impaired periosteal and endosteal bone formation and increased endosteal resorption (13).…”
mentioning
confidence: 99%
“…As patients enter their early teenage years, several require orthodontic intervention due to a malocclusion that may develop as a result of delayed eruption and loss of teeth due to caries. [8,9] Comparing radiological features from other cases in the literature, there was no significant difference in dental and other skeletal features (Table 1).…”
Section: Discussionmentioning
confidence: 78%
“…[8] The odontostomatological problems found in patients with Pyle disease are less important than their orthopaedic disorders, but they can stimulate the interest of the clinician to further investigate the possibility of the presence of a bone dysplasia. [8][9][10] Generally, craniofacial bones are only mildly affected. Often, an orthopantomographic radiograph is necessary to diagnose maxillofacial and dental deformities associated with this disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation